2019
DOI: 10.1111/jsr.12811
|View full text |Cite
|
Sign up to set email alerts
|

Associations between objectively measured and self‐reported sleep with academic and cognitive performance in adolescents: DADOS study

Abstract: Summary Adequate sleep has been positively related with health and school achievement outcomes during adolescence. The aim of this study was to investigate the associations of objectively measured and self‐reported sleep duration and quality with academic and cognitive performance in adolescents. This study was conducted with 257 adolescents (13.9 ± 0.3 years) from the DADOS study (Deporte, ADOlescencia y Salud). Objectively measured and self‐reported sleep duration and quality were obtained by a wrist‐worn GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
(69 reference statements)
0
22
2
Order By: Relevance
“…PA and sleep were measured using ActiGraph tri-axial accelerometers (ActiGraph, Pensacola, FL, USA), including wGT3X-BT and GT9X Link for children and adolescents, respectively. Both scientific-grade accelerometers are commonly used in the PA [ 23 – 25 ] and sleep [ 26 , 27 ] research and provide reliable and valid measures [ 28 30 ]. The participants wore the accelerometer on the non-dominant wrist for 24 h/day for 7 consecutive days, except when bathing, swimming, and performing personal hygiene.…”
Section: Methodsmentioning
confidence: 99%
“…PA and sleep were measured using ActiGraph tri-axial accelerometers (ActiGraph, Pensacola, FL, USA), including wGT3X-BT and GT9X Link for children and adolescents, respectively. Both scientific-grade accelerometers are commonly used in the PA [ 23 – 25 ] and sleep [ 26 , 27 ] research and provide reliable and valid measures [ 28 30 ]. The participants wore the accelerometer on the non-dominant wrist for 24 h/day for 7 consecutive days, except when bathing, swimming, and performing personal hygiene.…”
Section: Methodsmentioning
confidence: 99%
“…Previous systematic reviews and meta-analysis have shown that higher physical activity levels 4 , lower levels of sedentary behaviours (mainly recreational screen time) 5 , and optimal sleep duration 6 have been positively and independently related to academic achievement in children and adolescents. Physical activity has been shown to be more strongly associated with academic achievement among females than males 7 ; however, the few existing studies that have examined sex differences in the relationship between screen time 8 or sleep duration 9 and academic achievement have found inconsistent results. Therefore, further studies that examine the relationship of sleep duration and screen time with academic achievement in both males and females are required.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the common knowledge of needing sleep to perform well in school, many questions surrounding the relationship between sleep and academic performance remain such as the importance of bedtimes, sleep duration and sleep quality [8]. For example, in a study of adolescents, self-reported sleep quality and accelerometer measured sleep duration were associated with academic performance, but not self-reported sleep duration and accelerometer measured quality of sleep, [11] highlighting a need to better understand the relationship between sleep behaviour and academic performance.…”
Section: Introductionmentioning
confidence: 99%